Nasljednopravna stvar s prekograničnim elementom i nadležnost u okviru Uredbe (EU) br. 650/2012 o nasljeđivanju : neka hrvatska i slovenska iskustva i dvojbe - Aras Kramar, Slađana (Array, 2020)
After four years since Regulation (EU) No 650/2012 of the European Parliament and of the Council of 4 July 2012 on jurisdiction, applicable law, recognition and enforcement of decisions and acceptance and enforcement of authentic instruments in matters of successions and on the creation of a European Certificate of Succession has been implemented, in the paper certain theoretical, as well as implementationpractical issues will be analysed and discussed, based on the results of an empirical study on the implementation of the Regulation in Croatia and Slovenia during May – September 2019. The aim of the research is to detect and analyse the deficiencies of the existing normative regulation and problems in the implementation of the Regulation through the analysis of the normative framework of the Regulation, as well as European and national, Croatian and Slovenian implementing regulations and the experience of three groups of Croatian and Slovenian practitioners (judges, notaries, attorneys-at-law). After introductory remarks on the subject matter and methodology of the research, in the paper the succession matter with a cross-border element, the material scope of the Regulation and its relation to other European regulations are determined. Then follows the part of the paper on the principle of the unity of the estate, in which certain issues with situations of the existence of property constituting the estate in third states are discussed, especially in neighbouring post-Yugoslav states. Within the fourth part of the paper on the jurisdiction, the issues of determining the habitual residence in practice, the challenges faced by the competent authorities in determining jurisdiction based on that link are analysed and discussed, as well as specific issues with the agreement on the choice-of-court.